VD_FINDINFO Jug / 2012 / 86 vom 27. Oktober 2011 - VD Tribunal cantonal (2011)
VIOL, ACTE D'ORDRE SEXUEL AVEC UN ENFANT, PEINE COMPLÉMENTAIRE | 187 ch. 1 CP, 19 al. 2 CP, 190 al. 1 CP, 40 CP, 42 CP, 44 CP, 47 CP, 48a CP, 49 al. 1 CP, 49 al. 2 CP